Impact of population aging on trends in diabetes prevalence: A meta‐regression analysis of 160, 000 Japanese adults. Issue 5 (2nd March 2015) - Charvat, Hadrien; Goto, Atsushi; Goto, Maki; Inoue, Machiko; Heianza, Yoriko; Arase, Yasuji; Sone, Hirohito; Nakagami, Tomoko; Song, Xin; Qiao, Qing; Tuomilehto, Jaakko; Tsugane, Shoichiro; et al.
Abstract Aims/Introduction To provide age‐ and sex‐specific trends, age‐standardized trends, and projections of diabetes prevalence through the year 2030 in the Japanese adult population. Materials and Methods In the present meta‐regression analysis, we included 161, 087 adults from six studies and nine national health surveys carried out between 1988 and 2011 in Japan. We assessed the prevalence of diabetes using a recorded history of diabetes or, for the population of individuals without known diabetes, either a glycated hemoglobin level of ≥6.5% (48 mmol/mol) or the 1999 World Health Organization criteria (i.e., a fasting plasma glucose level of ≥126 mg/dL and/or 2‐h glucose level of ≥200 mg/dL in the 75‐g oral glucose tolerance test). Results For both sexes, prevalence appeared to remain unchanged over the years in all age categories except for men aged 70 years or older, in whom a significant increase in prevalence with time was observed. Age‐standardized diabetes prevalence estimates based on the Japanese population of the corresponding year showed marked increasing trends: diabetes prevalence was 6.1% among women (95% confidence interval [CI] 5.5–6.7), 9.9% (95% CI 9.2–10.6) among men, and 7.9% (95% CI 7.5–8.4) among the total population in 2010, and was expected to rise by 2030 to 6.7% (95% CI 5.2–9.2), 13.1% (95% CI 10.9–16.7) and 9.8% (95% CI 8.5–12.0), respectively. In contrast, the age‐standardized diabetes prevalence using a fixed population appeared to remain unchanged. Conclusions This large‐scale meta‐regression analysis shows that a substantial increase in diabetes prevalence is expected in Japan during the next few decades, mainly as a result of the aging of the adult population.